Hubungan Penggunaan Air Gambut dengan Keluhan Kulit yang Terjadi pada Masyarakat Desa Handil Sohor, Indonesia - Nawan, Nawan; Wulandari, Intan Wahyu; Alexandra, Francisca Diana; Handayani, Septi (Jurnal Biomedika dan Kesehatan, 2023)
Background The use of peat water as a water source, especially in areas with large peatlands, such as in central Kalimantan, is still common. Handil Sohor is one of the villages in Central Kalimantan Province where the community still uses peat water for daily needs. Peat water, which does not fulfill the health requirement, is used for daily needs such as bathing and washing; therefore it can cause health complaints on the skin. Purpose of this study was to determine the correlation between peat water and skin disease complaints that happened in society. Methods The research type used is an analytical descriptive method with a cross-sectional design. The samples used in this research are 116 people taken with the purposive sampling technique and peat water samples. This research is conducted in June - October 2022. Results This research results showed that in a society with a contact duration of more than 60 minutes/day experienced skin disease complaints are 32 respondents in a society with a frequency of using peat water more than three times/day who experienced skin disease complaints are 41 respondents. The statistical test results through the chi-square test obtained the results for the contact duration variable with scores (p-value = 0,007) and (OR = 2,857). Conclusions Contact duration and frequency of use of peat water correlate with skin disease complaints.